Cultura e comprometimento organizacional: um estudo de caso no segmento de condutores elétricos - Sant’anna, Dalmir Antonio de (2013)
This study is predicated on two criteria: organizational culture and organizational commitment. The aim was to analyze how the culture of an organization in the electrical cable and conductor industry could be related to the organizational commitment of the professional staff working in the commercial area. In terms of the methodology, the study is based on both quantitative and qualitative approaches. The data were collected through the application of questionnaires, semi-structured interviews and an analysis of documentation. In order to evaluate organizational culture, the Brazilian Instrument for Evaluating Organizational Culture (IBACO) was used, validated by Ferreira & Assmar (2008). To evaluate the commitment of an organization, the Organizational Commitment Scale (EBACO) was used, validated by Bastos et al. (2008). Data treatment and analysis were performed by means of descriptive statistics and content analysis techniques. By using different sources of evidence (interviews, questionnaires and document analysis), it was possible to carry out a triangulation of the data, contributing to an understanding of the relationship between culture and commitment in the context in question, as well as to identify consistency between the values declared by the organization and perceived values, which, according to the literature, contributes to the involvement and commitment of the employee and behavior based on these values. We identified the influence of the values and practices of organizational culture on the commitment of sales professionals. The values of cooperative professionalism and the practices of fostering interpersonal relationships stood out in the organizational culture construct and the bases of attachment, obligation for performance and associative obligation were prominent in the organizational commitment construct. The results indicated that a sales force, even when independent, can demonstrate commitment through the values of cooperative professionalism, employee satisfaction and wellbeing as well as practices to foster interpersonal relationships, external integration, rewards and training.